Antibacterial ABS composite material and preparation method thereof

By using parathrax/Fe2O3/cubic chromate composite as antibacterial agent in ABS composites, the problem of insufficient antibacterial performance of existing ABS composites is solved, and efficient bacterial inhibition effect is achieved, and it is suitable for automotive interiors with high antibacterial requirements.

CN119529465AInactive Publication Date: 2025-02-28HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311087586.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The application of existing ABS composite materials in automotive interiors and other fields is subject to insufficient antibacterial performance, especially when the antibacterial rate of more than 97%, the existing technology is difficult to meet this requirement.

Method used

The antibacterial ABS composite is prepared by specific synthetic methods to improve its antibacterial properties.

Benefits of technology

The antibacterial rate for conventional bacteria such as Staphylococcus aureus has reached more than 99%, which is significantly higher than the previous requirements and is suitable for automotive and home appliance materials fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004416580450000091
    Figure BDA0004416580450000091
Patent Text Reader

Abstract

The invention discloses an antibacterial ABS (Acrylonitrile Butadiene Styrene) composite material and a preparation method thereof. The antibacterial ABS composite material is prepared from the following components in parts by weight: 80-100 parts of ABS, 2-6 parts of an antibacterial agent and 0.1-0.5 part of an antioxidant, wherein the antibacterial agent is a palygorskite / Fe2O3 / copper chromate compound. The invention also discloses a preparation method of the ABS composite material. The antibacterial agent palygorskite / Fe2O3 / copper chromate compound is added, so that cell membranes of escherichia coli are destroyed by releasing Fe < 3 + > and Cu < 2 + >, and bacteria are killed. The antibacterial rate of the prepared ABS composite material to conventional staphylococcus aureus and the like can reach 99% or above and is remarkably higher than 97% required, and the ABS composite material can be used in the field of automobile household appliance materials and has excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to an antibacterial ABS composite material and a preparation method thereof. Background Art

[0002] Acrylonitrile-butadiene-styrene resin (ABS) is a widely used high molecular polyester resin. ABS has the advantages of good fatigue resistance, heat resistance, and excellent dimensional stability. However, in some specific application fields, the antibacterial performance of ABS is very high, which will limit the application of ABS composite materials in some specific fields. For example, it is used as automotive interior decoration (seats, steering wheels, instrument panels, door panels, etc.), but since these interior decoration parts are in direct contact with people, thermoplastic resins are required to have good antibacterial properties, so as to effectively inhibit the growth and spread of bacteria and viruses, and also avoid the growth of bacteria and microorganisms to produce odors, stains, and damage to materials. Although there are also environmentally friendly antibacterial agents such as chitosan added to ABS to improve antibacterial properties, it still cannot meet the requirement that the antibacterial rate of automotive interior decoration parts must reach more than 97%.

[0003] In view of these shortcomings, the present invention innovatively synthesizes a novel antibacterial ABS composite material, which has excellent antibacterial properties. This ABS composite material has not been reported so far, which has very important practical significance for expanding the application field of ABS composite materials. Summary of the invention

[0004] In view of this, the present invention provides an antibacterial ABS composite material and a preparation method thereof, which has excellent antibacterial performance and performance, and solves the technical problems of limited ABS performance and antibacterial ability in the prior art.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] An antibacterial ABS composite material, which consists of the following components in parts by weight:

[0007] ABS 80-100 copies

[0008] 2-6 parts of antibacterial agent

[0009] Antioxidant 0.1-0.5 parts

[0010] The antibacterial agent is a palygorskite / Fe2O3 / copper chromate complex.

[0011] The preparation method of the antibacterial agent palygorskite / Fe2O3 / copper chromate composite comprises the following steps:

[0012] (1) reacting palygorskite, solvent, iron salt and sodium hydroxide at 70-90° C. for 6-8 hours, filtering and drying the reaction product to obtain product A;

[0013] (2) placing the product A in a muffle furnace and calcining it to obtain palygorskite / Fe2O3;

[0014] (3) Add palygorskite / Fe2O3, sodium chromate and copper nitrate into deionized water, react at 60-80°C for 6-10 hours, filter and dry the reaction product to obtain a palygorskite / Fe2O3 / copper chromate complex.

[0015] Preferably, the drying in step (1) refers to drying in an oven at 60-80° C. for 6-10 hours;

[0016] The mass ratio of the palygorskite, the solvent, the iron salt and the sodium hydroxide is (50-60):(180-240):(30-40):(30-36).

[0017] Drying in step (1) means drying in an oven at 60-80°C for 6-10 hours;

[0018] Preferably, the calcination in step (2) refers to calcination at 680-720° C. for 10-14 h.

[0019] In step (3), the drying step is performed by placing the product in an oven at 70-80°C for 8-10 hours.

[0020] The mass ratio of palygorskite / Fe2O3, sodium chromate, copper nitrate and deionized water is (60-80):(30-36):(36-40):(100-160).

[0021] The antioxidant is one or a mixture of 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamino)phenol (Irganox 565), N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)) (Irganox 1098) and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (Irganox 1330).

[0022] The second object of the present invention is to provide a method for preparing the above antibacterial ABS composite material, comprising the following steps:

[0023] (1) Weigh 80-100 parts of ABS, 2-6 parts of antibacterial agent, and 0.1-0.5 parts of antioxidant, mix and stir evenly to obtain a mixture;

[0024] (2) Extruding the mixture obtained in step (1) from an extruder and granulating it to obtain an ABS composite material.

[0025] Preferably, the twin-screw extruder in step (2) comprises six temperature zones arranged in sequence, with the temperature of zone one being 200-220°C, the temperature of zone two being 240-260°C, the temperature of zone three being 240-260°C, the temperature of zone four being 240-260°C, the temperature of zone five being 240-260°C, the temperature of zone six being 240-260°C, the temperature of the die head being 240-260°C, and the screw speed being 200-280 r / min.

[0026] Taking ferric nitrate as an example in this application, the reaction process of the antibacterial agent is as follows:

[0027] Fe(NO3)3+NaOH→Fe(OH)3+3NaNO3

[0028] 2Fe(OH)3→Fe2O3+3H2O

[0029] Na2CrO4+Cu(NO3)2→2NaNO3+CuCrO4

[0030] That is, a palygorskite / Fe2O3 / copper chromate complex is obtained.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The antibacterial mechanism of the palygorskite / Fe2O3 / copper chromate composite synthesized in the present invention is as follows: the palygorskite is used as a carrier, and the copper chromate in the palygorskite / Fe2O3 / copper chromate is positively charged when it encounters water, and exhibits positive affinity when it encounters negatively charged Escherichia coli, which is conducive to inducing bacteria to aggregate on the surface of the material, and then releases Fe 3+ , Cu 2+ It destroys the cell membrane of E. coli, thus killing the bacteria.

[0033] (2) The antibacterial rate of the ABS composite material prepared by the present invention against conventional Staphylococcus aureus and the like can reach over 99%, which is significantly higher than the required 97%, and can be used in the field of automotive and household appliance materials, with excellent application prospects. DETAILED DESCRIPTION

[0034] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0036] The raw materials used in the following examples are as follows:

[0037] ABS (model 750A), Daqing Petrochemical;

[0038] Deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.;

[0039] Acetone, Jinan Wenzhu Chemical Co., Ltd.;

[0040] Copper nitrate, Shandong Xuxiang Chemical Co., Ltd.;

[0041] Palygorskite, Chongqing Shihuan Mining Co., Ltd.;

[0042] Sodium hydroxide, Jinan Qinghai Chemical Co., Ltd.;

[0043] Sodium chromate, Jinan Yuansu Chemical Co., Ltd.; Ferric nitrate, Shandong Xuxiang Chemical Co., Ltd.;

[0044] Antioxidants (models Irganox565, Irganox1098, Irganox1330), BASF;

[0045] Chitosan, Jiangsu Caiwei Biotechnology Co., Ltd.

[0046] Preparation Example 1

[0047] (1) Weigh 500 g of palygorskite, 1.8 kg of acetone, 300 g of ferric nitrate, and 300 g of sodium hydroxide, place them in a reaction vessel, react at 70° C. for 6 h, filter the reaction product, and place it in an oven at 60° C. to dry for 6 h to obtain product A;

[0048] (2) calcining product A at 680°C in a muffle furnace for 10 h to obtain palygorskite / Fe2O3;

[0049] (3) Weigh 600 g of palygorskite / Fe2O3, 300 g of sodium chromate, 360 g of copper nitrate, and 1.0 kg of deionized water, place them in a reaction vessel, react at 60°C for 6 h, filter the reaction product, and dry it in an oven at 70°C for 8 h to obtain a palygorskite / Fe2O3 / copper chromate complex, which is recorded as antibacterial agent M1.

[0050] Example 1

[0051] (1) Weigh 80 parts of ABS, 2 parts of antimicrobial agent M1, and 0.1 parts of Irganox 1098, mix and stir evenly to obtain a mixture;

[0052] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material P1.

[0053] The twin-screw extruder comprises six temperature zones arranged in sequence, with the temperature of zone one at 200°C, the temperature of zone two at 240°C, the temperature of zone three at 240°C, the temperature of zone four at 240°C, the temperature of zone five at 240°C, the temperature of zone six at 240°C, the temperature of the die head at 240°C, and the screw speed at 200r / min.

[0054] Preparation Example 2

[0055] (1) Weigh 600 g of palygorskite, 2.4 kg of acetone, 400 g of ferric nitrate, and 360 g of sodium hydroxide, place them in a reaction vessel, react at 90° C. for 8 h, filter the reaction product, and dry it in an oven at 80° C. for 10 h to obtain product A.

[0056] (2) Product A was calcined at 720°C in a muffle furnace for 14 h to obtain palygorskite / Fe2O3.

[0057] (3) Weigh 800 g of palygorskite / Fe2O3, 360 g of sodium chromate, 400 g of copper nitrate, and 1.6 kg of deionized water, place them in a reaction vessel, react at 80°C for 10 h, filter the reaction product, and dry it in an oven at 80°C for 10 h to obtain a palygorskite / Fe2O3 / copper chromate complex, which is recorded as antibacterial agent M2.

[0058] Example 2

[0059] (1) Weigh 100 parts of ABS, 6 parts of antibacterial agent M2, 0.1 parts of antioxidant Irganox 1098, 0.2 parts of antioxidant Irganox 565, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0060] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material P2.

[0061] The twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 220°C, the temperature of zone two at 260°C, the temperature of zone three at 260°C, the temperature of zone four at 260°C, the temperature of zone five at 260°C, the temperature of zone six at 260°C, the head temperature at 260°C, and the screw speed at 280r / min.

[0062] Preparation Example 3

[0063] (1) Weigh 550 g of palygorskite, 2.1 kg of acetone, 350 g of ferric nitrate, and 330 g of sodium hydroxide, place them in a reaction vessel, react at 80° C. for 7 h, filter the reaction product, and dry it in an oven at 70° C. for 8 h to obtain product A.

[0064] (2) Product A was calcined at 700°C in a muffle furnace for 12 h to obtain palygorskite / Fe2O3.

[0065] (3) Weigh 700 g of palygorskite / Fe2O3, 330 g of sodium chromate, 380 g of copper nitrate, and 1.3 kg of deionized water, place them in a reaction vessel, react at 70°C for 8 h, filter the reaction product, and dry it in an oven at 75°C for 9 h to obtain a palygorskite / Fe2O3 / copper chromate complex, which is recorded as antibacterial agent M3.

[0066] Example 3

[0067] (1) Weigh 90 parts of ABS, 4 parts of antibacterial agent N3, 0.1 parts of antioxidant Irganox565, and 0.2 parts of antioxidant Irganox1098, mix and stir to obtain a mixture;

[0068] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material P3.

[0069] The twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 215°C, the temperature of zone two at 255°C, the temperature of zone three at 255°C, the temperature of zone four at 255°C, the temperature of zone five at 255°C, the temperature of zone six at 255°C, the head temperature at 255°C, and the screw speed at 245r / min.

[0070] Preparation Example 4

[0071] (1) Weigh 585 g of palygorskite, 1.95 kg of acetone, 395 g of ferric nitrate, and 345 g of sodium hydroxide, place them in a reaction vessel, react at 85° C. for 8 h, filter the reaction product, and dry it in an oven at 75° C. for 9 h to obtain product A.

[0072] (2) Product A was calcined at 715°C in a muffle furnace for 13 h to obtain palygorskite / Fe2O3.

[0073] (3) Weigh 755 g of palygorskite / Fe2O3, 355 g of sodium chromate, 395 g of copper nitrate, and 1.45 kg of deionized water, place them in a reaction vessel, react at 75°C for 10 h, filter the reaction product, and dry it in an oven at 80°C for 8 h to obtain a palygorskite / Fe2O3 / copper chromate complex, which is recorded as antibacterial agent M4.

[0074] Example 4

[0075] (1) Weigh 85 parts of ABS, 4 parts of antibacterial agent N4, 0.1 parts of antioxidant Irganox 1098, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;

[0076] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material P4.

[0077] The twin-screw extruder includes six temperature zones arranged in sequence, with zone one at 215°C, zone two at 245°C, zone three at 245°C, zone four at 245°C, zone five at 245°C, zone six at 245°C, die head temperature at 245°C, and screw speed at 245r / min.

[0078] Preparation Example 5

[0079] (1) Weigh 555 g of palygorskite, 1.85 kg of ethanol, 395 g of ferric sulfate, and 355 g of sodium hydroxide, place them in a reaction vessel, react at 70° C. for 8 h, filter the reaction product, and dry it in an oven at 65° C. for 10 h to obtain product A.

[0080] (2) Product A was calcined at 715°C in a muffle furnace for 14 h to obtain palygorskite / Fe2O3.

[0081] (3) Weigh 755 g of palygorskite / Fe2O3, 325 g of sodium chromate, 395 g of copper nitrate, and 1.55 kg of deionized water, place them in a reaction vessel, and react at 75°C for 8 h. Filter the reaction product and dry it in an oven at 75°C for 9 h to obtain a palygorskite / Fe2O3 / copper chromate complex, which is recorded as antibacterial agent M5.

[0082] Example 5

[0083] (1) Weigh 95 parts of ABS, 3.5 parts of antibacterial agent M5, 0.1 parts of antioxidant Irganox 1098, and 0.1 parts of antioxidant Irganox 565, mix and stir to obtain a mixture;

[0084] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material P5.

[0085] The twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 215°C, the temperature of zone two at 255°C, the temperature of zone three at 255°C, the temperature of zone four at 255°C, the temperature of zone five at 255°C, the temperature of zone six at 255°C, the head temperature at 255°C, and the screw speed at 255r / min.

[0086] Comparative Example 1

[0087] (1) Weigh 95 parts of ABS, 0.1 parts of antioxidant Irganox 1098, and 0.1 parts of antioxidant Irganox 565, mix and stir evenly to obtain a mixture;

[0088] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material D1.

[0089] The twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 215°C, the temperature of zone two at 255°C, the temperature of zone three at 255°C, the temperature of zone four at 255°C, the temperature of zone five at 255°C, the temperature of zone six at 255°C, the head temperature at 255°C, and the screw speed at 255r / min.

[0090] Comparative Example 2

[0091] (1) Weigh 95 parts of ABS, 3.5 parts of commercial chitosan antibacterial agent, 0.1 parts of antioxidant Irganox 1098, and 0.1 parts of antioxidant Irganox 565, mix and stir to obtain a mixture;

[0092] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain an ABS composite material D2.

[0093] The twin-screw extruder includes six temperature zones arranged in sequence, with the temperature of zone one at 215°C, the temperature of zone two at 255°C, the temperature of zone three at 255°C, the temperature of zone four at 255°C, the temperature of zone five at 255°C, the temperature of zone six at 255°C, the head temperature at 255°C, and the screw speed at 255r / min.

[0094] The ABS composite materials prepared in the above Examples 1-5 and Comparative Example 2 were made into test strips by an injection molding machine, and then their antibacterial properties were tested. The specific data are as follows:

[0095]

[0096] It can be seen from the above table that the antibacterial properties of Examples 1 to 5 are better than those of Comparative Examples 1 to 2. This shows that the ABS composite material prepared by the method provided by the present invention has excellent antibacterial properties and can expand the application field of the ABS composite material.

[0097] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0098] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An antibacterial ABS composite material, characterized in that: It is composed of the following components by weight: ABS 80-100 copies Antibacterial agent 2-6 parts Antioxidant 0.1-0.5 parts The antibacterial agent is a palygorskite / Fe2O3 / copper chromate complex.

2. The antibacterial ABS composite material according to claim 1, characterized in that: The preparation method of the antibacterial agent palygorskite / Fe2O3 / copper chromate composite comprises the following steps: (1) reacting palygorskite, solvent, iron salt and sodium hydroxide at 70-90° C. for 6-8 hours, filtering and drying the reaction product to obtain product A; (2) placing the product A in a muffle furnace and calcining it to obtain palygorskite / Fe2O3; (3) Add palygorskite / Fe2O3, sodium chromate and copper nitrate into deionized water, react at 60-80°C for 6-10 hours, filter and dry the reaction product to obtain a palygorskite / Fe2O3 / copper chromate complex.

3. The antibacterial ABS composite material according to claim 2, characterized in that: Drying in step (1) means drying in an oven at 60-80°C for 6-10 hours; The mass ratio of the palygorskite, the solvent, the iron salt and the sodium hydroxide is (50-60):(180-240):(30-40):(30-36).

4. The antibacterial ABS composite material according to claim 2, characterized in that: The solvent in step (1) is acetone, ethanol or ether; The iron salt is ferric nitrate, ferric phosphate, ferric chloride or ferric sulfate.

5. The antibacterial ABS composite material according to claim 2, characterized in that: The calcination in step (2) refers to calcination at 680-720° C. for 10-14 hours.

6. The antibacterial ABS composite material according to claim 2, characterized in that: The drying in step (3) is carried out by placing the product in an oven at 70-80°C for 8-10 hours.

7. The antibacterial ABS composite material according to claim 2, characterized in that: The mass ratio of palygorskite / Fe2O3, sodium chromate, copper nitrate and deionized water is (60-80):(30-36):(36-40):(100-160).

8. The antibacterial ABS composite material according to claim 1, characterized in that: The antioxidant is one of 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamino)phenol, N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)) and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene or a mixture of several thereof.

9. A method for preparing an antibacterial ABS composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Weigh 80-100 parts of ABS, 2-6 parts of antibacterial agent, and 0.1-0.5 parts of antioxidant, mix and stir evenly to obtain a mixture; (2) Extruding the mixture obtained in step (1) through a twin-screw extruder to form granules, thereby obtaining an ABS composite material.

10. The preparation method according to claim 9, characterized in that: In step (2), the twin-screw extruder includes six temperature zones arranged in sequence, wherein the temperature of zone one is 200-220°C, the temperature of zone two is 240-260°C, the temperature of zone three is 240-260°C, the temperature of zone four is 240-260°C, the temperature of zone five is 240-260°C, the temperature of zone six is ​​240-260°C, the head temperature is 240-260°C, and the screw speed is 200-280r / min.

Citation Information

Patent Citations

  • Flame-retardant antibacterial ABS composite material and preparation method thereof

    CN116285202A

  • Antibacterial PI composite material and preparation method thereof

    CN116535856A